1984
DOI: 10.1084/jem.160.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Molecular localization of human class II MT2 and MT3 determinants.

Abstract: The antigens encoded in the HLA-D region of the human major histocompatibility complex (MHC) 1 were originally defined with homozygous typing cells by mixed leukocyte culture and, subsequently, by use of human alloantisera reacting with antigens selectively expressed on B cells (1, 2). These antigens were later shown to be the human equivalents of the murine Ia molecules. The major serologically defined specificities, called DR, were found to be closely associated with the specificities defined by HTCs. Later,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…As shown in Table I, the monoclonal antibody l09d6 reacted with an epitope expressed on the blasts found in 85% of 77 acute myelogenous leukemia patients but only in 40.5% of controls, relative risk (RR) = +7.88, population attributable risk (b) = 0.75, P < 0.000005 (uncorrected). In a healthy caucasian control population, the molecule bearing the l09d6 determinant is usually found in association with the HLA DRw53 allospecificity determined by polyclonal typing reagents, r = 0.724 (20), but in the leukemic group the frequency of HLA DRw53 was slightly, but not significantly, increased. In the control Caucasian population, the presence of the 17-3-3S determinant is associated with the presence ofthe l09d6 determinant, r = 0.783.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table I, the monoclonal antibody l09d6 reacted with an epitope expressed on the blasts found in 85% of 77 acute myelogenous leukemia patients but only in 40.5% of controls, relative risk (RR) = +7.88, population attributable risk (b) = 0.75, P < 0.000005 (uncorrected). In a healthy caucasian control population, the molecule bearing the l09d6 determinant is usually found in association with the HLA DRw53 allospecificity determined by polyclonal typing reagents, r = 0.724 (20), but in the leukemic group the frequency of HLA DRw53 was slightly, but not significantly, increased. In the control Caucasian population, the presence of the 17-3-3S determinant is associated with the presence ofthe l09d6 determinant, r = 0.783.…”
Section: Resultsmentioning
confidence: 99%
“…Both chains of the Ia molecules are encoded by genes found in three subregions: DR, DQ (DC or DS), and DP (SB) (20). Two polymorphic O-chain sequences and one nonpolymorphic a-chain are thought to be encoded in the DR subregion, while the more centromeric DQ subregion contains two pairs of polymorphic a-chain and 0-chain genes; the DP subregion is similarly organized (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Although these latter MoAb thus appear to have an identical specificity, several investigators have demonstrated that they are detecting different determinants. Binding of the I-LR2 MoAb can be inhibited by preincubation with the 7.3.19.1 MoAb on DR3+ cells but not on DR5+cells [3], whereas I-LR2and7. 3.19.1 react with mutually exclusive subsets of DR-like molecules on DR5+ and DRw6+ cells [4].…”
mentioning
confidence: 94%
“…DR family-associated Ia determinants can be divided into two series based on their population distributions; recent evidence potentially relates them to different aO diners of DR. The DRI thru DRwl4 specificities are thought to be associated with one of the DR dimers, arbitrarily aBi, whereas as the DRy52 and DRw53 (previously referred to as MT2 and MT3) specificities are thought to be related to an Ci2 diner (Hurley et al, 1984). Although the associations with a81 have been examined for only certain of the DRl thru DRwl4 antigens, and there should therefore be some hesitation in accepting these assignments too firmly, we shall use this concept in the article.…”
Section: Class 11 Phenotyping Vith Alloantisera and Homozygous Typingmentioning
confidence: 99%